2021
DOI: 10.3390/jcm10030504
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Could Be a Potential Prognostic Factor in Ambulatory Elderly Patients with Stable Heart Failure: Results from a Pilot Study

Abstract: Introduction: Inflammation is a fundamental phenomenon in heart failure, but the prognostic or therapeutic role of markers such as interleukin-6 (IL-6) has not yet been clarified. The objective of this study is to describe the clinical profile of patients with elevated IL-6 and determine if they have worse clinical outcomes. Methods: A retrospective c.ohort observational study including 78 patients with heart failure followed up at the Heart Failure Outpatient Clinic of the Internal Medicine Department. IL-6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…3 However, the majority of data pertaining to IL-6 (and IL-1/1β, its upstream signaling precursor) in prevalent heart failure are from patients with heart failure with reduced ejection fraction (HFrEF) or all-comers with heart failure in whom ejection fraction is undefined. 8,[13][14][15][16][17][18][19][20] The CANTOS trial (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) reported that, in patients with a history of prior myocardial infarction and elevated hsCRP (high-sensitivity CRP), treatment with the IL-1β inhibitor, canakinumab, reduced heart failure hospitalization and heart failurerelated mortality, although an examination of these effects specifically upon HFpEF was not addressed. 10,11 ZEUS (Ziltivekimab Cardiovascular Outcomes Study) is a large phase 3 trial examining the effect of IL-6 inhibition upon cardiovascular outcomes in patients with chronic kidney disease and elevated hsCRP.…”
mentioning
confidence: 99%
“…3 However, the majority of data pertaining to IL-6 (and IL-1/1β, its upstream signaling precursor) in prevalent heart failure are from patients with heart failure with reduced ejection fraction (HFrEF) or all-comers with heart failure in whom ejection fraction is undefined. 8,[13][14][15][16][17][18][19][20] The CANTOS trial (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) reported that, in patients with a history of prior myocardial infarction and elevated hsCRP (high-sensitivity CRP), treatment with the IL-1β inhibitor, canakinumab, reduced heart failure hospitalization and heart failurerelated mortality, although an examination of these effects specifically upon HFpEF was not addressed. 10,11 ZEUS (Ziltivekimab Cardiovascular Outcomes Study) is a large phase 3 trial examining the effect of IL-6 inhibition upon cardiovascular outcomes in patients with chronic kidney disease and elevated hsCRP.…”
mentioning
confidence: 99%
“…IL-6 and TNF-α are proinflammatory cytokines produced mostly by activated monocytes and macrophages. The proinflammatory role of these cytokines in systemic inflammation is well established in various pathologies, including cardiovascular diseases such as atherosclerotic cardiovascular disease and chronic heart failure [48,49]. In addition, the prognostic role of IL-6 and TNF-α in chronic heart failure patients has been demonstrated in previous studies [50,51].…”
Section: Discussionmentioning
confidence: 91%
“…13 Specifically, IL-6 has been found to be more prevalent in elderly patients with a higher burden of cardiovascular co-morbidities and is associated with increased mortality in HF. 14 A post hoc analysis of the PARAGON-HF (Prospective Comparison of ARNI [angiotensin receptor-neprilysin inhibitor] with ARB [angiotensin receptor blocker] Global Outcomes in HF with Preserved Ejection Fraction) trial showed an increasing neutrophil-to-lymphocyte ratio, a marker of systemic inflammation, with worsening frailty in HF patients. 15 Systemic inflammation also leads to progression of atherosclerosis and insulin resistance, and changes in metabolic hormonal activity such as insulin growth factor and growth differentiation factor 15 (GDF-15), which also contribute towards worsening frailty.…”
Section: Mechanisms For Frailty In Heart Failurementioning
confidence: 99%
“…Pro‐inflammatory markers, such as C‐reactive protein, tissue necrosis factor and interleukin‐6 (IL‐6), are elevated in HF and are associated with a heightened risk of HF in the elderly 13 . Specifically, IL‐6 has been found to be more prevalent in elderly patients with a higher burden of cardiovascular co‐morbidities and is associated with increased mortality in HF 14 . A post hoc analysis of the PARAGON‐HF (Prospective Comparison of ARNI [angiotensin receptor–neprilysin inhibitor] with ARB [angiotensin receptor blocker] Global Outcomes in HF with Preserved Ejection Fraction) trial showed an increasing neutrophil‐to‐lymphocyte ratio, a marker of systemic inflammation, with worsening frailty in HF patients 15 .…”
Section: Mechanisms For Frailty In Heart Failurementioning
confidence: 99%